Burmannic Acid Inhibits Proliferation and Induces Oxidative Stress Response of Oral Cancer Cells - Su-Ling Liu; Kun-Han Yang; Che-Wei Yang; Min-Yu Lee; Ya-Ting Chuang; Yan-Ning Chen; Fang-Rong Chang; Chung-Yi Chen; Hsueh-Wei Chang (MDPI AG, 2021)
Burmannic acid (BURA) is a new apocarotenoid bioactive compound derived from Indonesian cinnamon; however, its anticancer effect has rarely been investigated in oral cancer cells. In this investigation, the consequences of the antiproliferation of oral cancer cells effected by BURA were evaluated. BURA selectively suppressed cell proliferation of oral cancer cells (Ca9-22 and CAL 27) but showed little cytotoxicity to normal oral cells (HGF-1). In terms of mechanism, BURA perturbed cell cycle distribution, upregulated mitochondrial superoxide, induced mitochondrial depolarization, triggered γH2AX and 8-hydroxy-2-deoxyguanosine DNA damage, and induced apoptosis and caspase 3/8/9 activation in oral cancer cells. Application of N-acetylcysteine confirmed oxidative stress as the critical factor in promoting antiproliferation, apoptosis, and DNA damage in oral cancer cells.